An Overview of Carbon Nanotubes and Graphene for Biosensing Applications - Zhu, Zanzan (Nano-Micro Letters, 2017)
With the development of carbon nanomaterials in recent years, there has been an explosion of interests in using carbon nanotubes (CNTs) and graphene for developing new biosensors. It is believed that employing CNTs and graphene as sensor components can make sensors more reliable, accurate, and fast due to their remarkable properties. Depending on the types of target molecular, different strategies can be applied to design sensor device. This review article summarized the important progress in developing CNT- and graphene-based electrochemical biosensors, field-effect transistor biosensors, and optical biosensors. Although CNTs and graphene have led to some groundbreaking discoveries, challenges are still remained and the state-of-the-art sensors are far from a practical application. As a conclusion, future effort has to be made through an interdisciplinary platform, including materials science, biology, and electric engineering.